Runway Lighting and Lighting Control Systems: Example of The Erzincan Airport - Mustafa Şahin (Journal of New Results in Science)
The purpose of this study; In order to perform a safe landing and takeoff of the aircraft, It is to examine the runway lighting system, light guidance elements and the control unit of these equipments. Based on this information in the study, of Erzincan airport runway lighting system has been examined. Runway lighting system are investigated as threshold lights, runway threshold identification lights, runway end lights, runway center line lights, runway edge lights, touchdown zone lights, taxiway edge lights, taxiway center line lights. Also, stop bars, approaching fixtures, runway fixtures, runway edge fixtures, beacon light system, PAPI and so on. Lighting components and related to them, are given extensive information about the control systems.